Pembaruan Pengaturan Pidana Demi Eradikasi Praktik Prostitusi - Assyifa, Lilia Safitri; Sitaputri, Kamila Maharani; Indradjaja, Nobella; Chamdani, Chamdani (Law and Humanity, 2024)
The rapid technological advancement nowadays accelerates the spread of various forms of information, including information regarding prostitution practices. Meanwhile, from a legal perspective, a complete regulation on prostitution practices is at its minimum, and thus the impacts of the prostitution practices affect health aspects and drives social turmoil in the community. This research aims to review regulations related to prostitution practices, especially in the applicable criminal law in Indonesia, and propose factors that emphasizes a law reform, so that in the future, prostitution practices may be handled more thoroughly. This research uses a normative method, with secondary data that includes literary research and reviews on laws and regulations as well as an analysis method that uses a prescriptive technique. The conclusion resulting from this research reveals that in reality, several regional regulations have regulated prostitution practices, but nationally, there has not been any regulation that strictly regulates prostitution practices. The suggestions proposed by the researcher for the future is in a preventive and repressive form, which are clear limitations of prostitution practices, criminal act reform for pimps, criminalization for commercial sex workers (PSK), the use of double-track system in imposing sanctions, criminal act formulation, and criminal aggravation.